2022
DOI: 10.1021/acs.nanolett.2c01736
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cyclability of Lithium Metal Anodes Enabled by Anti-aggregation of Lithiophilic Seeds

Abstract: Constructing 3D skeletons modified with lithiophilic seeds has proven effective in achieving dendrite-free lithium metal anodes. However, these lithiophilic seeds are mostly alloy-or conversion-type materials, and they tend to aggregate and redistribute during cycling, resulting in the failure of regulating Li deposition. Herein, we address this crucial but long-neglected issue by using intercalation-type lithiophilic seeds, which enable antiaggregation owing to their negligible volume expansion and high elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…More impressively, even if the current density increases to 10 mA cm −2 , the WDC-GDAg battery can still cycle over 200 h without short circuits, which is far beyond the cycling life of the WDC and Li foil (Figure 3e; Figure S16, Supporting Information). This remarkable cycling stability and rate performance endow the gradient-distributed 3D structures with great competitiveness among the everreported lithium metal modulation strategies in the latest literature [17,31,50,51,[67][68][69][70][71][72][73][74] (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…More impressively, even if the current density increases to 10 mA cm −2 , the WDC-GDAg battery can still cycle over 200 h without short circuits, which is far beyond the cycling life of the WDC and Li foil (Figure 3e; Figure S16, Supporting Information). This remarkable cycling stability and rate performance endow the gradient-distributed 3D structures with great competitiveness among the everreported lithium metal modulation strategies in the latest literature [17,31,50,51,[67][68][69][70][71][72][73][74] (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…Meanwhile, the spherical morphology of SiO x /C@C is well maintained after cycling, without dissolution or aggregation problems such as lithiophilic Au or Ag "seeds" (Figure S11, Supporting Information). [22,42] Reviewing the whole lithiation/Li plating process of yolk-shell SiO x /C@C as shown in Video S1, Supporting Information; Figure 3a, it is observed that the Li deposition always begins at the interface, that is to say, the contact point between SiO x /C core and N,S co-doped C shell (indicated by the red circle in Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…[ 17–21 ] The aggregation or dissolution of these materials during cycling will lead to insufficient regulation effects and inaccessible voids for Li deposition. Besides, some oxide‐based lithiophilic “sites” (TiO 2 , SiO x /C) have also been employed to regulate the Li deposition, demonstrating better structural stability than the above‐mentioned metallic lithiophilic “sites.” [ 22,23 ] Doping the carbon materials with foreign atoms can also improve the lithiophilicity; [ 24–26 ] however, as Li is deposited only on the surface of the hollow carbon without entering it, [ 27 ] Li dendrites will form as well when the deposited Li increases (Scheme 1b). Due to the insufficiently utilized void space, the Li storage capacities are usually low (<3 mAh cm −2 ) before the dendrite is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanofibers (CNFs) usually have high specific surface area, rich pore structure, excellent chemical stability, and high electrical conductivity and, as artificial protective layers, have been shown to effectively reduce local current density and regulate lithium deposition. For example, the carbonized silk nanofiber (SCNF) films were used as double interlayers of lithium-sulfur batteries, which could inhibit the growth of lithium dendrites on the LMA side and block dissolved polysulfides on the sulfur cathode side to reduce their corrosion to lithium metal (Figure a) . In addition, the doping of nanoparticles or nanosheets into carbon-based materials as heterogeneous seeds can effectively guide lithium deposition and achieve spatial control of lithium nucleation, which is a common tactic to enhance the lithiophilicity of carbon-based protective layers. As shown in Figure b, Wei and co-workers manufactured ordered carbon nanofiber films (MnS@CNC/CNFs) doped with MnS nanoparticles and cellulose nanocrystalline (CNC) by microfluidic spinning techniques and carbonization processes . The MnS nanoparticles in the fiber film underwent similar alloying reaction with Li + , and the polar functional group (−OH) in the CNC had a strong adsorption effect on Li + , which could guide Li + to be uniformly plated on the electrode surface, thus effectively inhibiting the formation of dendritic lithium (Figure c).…”
Section: Nanofibrous Materials For Artificial Protective Layersmentioning
confidence: 99%